AN ANALYSIS OF STUDENTS’ ENGLISH VOCABULARY LEARNING STRATEGIES AT THE SECOND SEMESTER OF ENGLISH DEPARTMENT AT MADAKO UNIVERSITY - Hidayati Hidayati; Bahria Bahria (Universitas Madako Tolitoli, 2022)
This research aimed at An Analysis of Students’ Vocabulary Learning Strategies at the second semester of English Department at Madako University. The design of this research was qualitative research. This research was conducted in Madako University. The samples were 10 students at class B which selected purposively. The data collected through interview and questionnaire. This research used five strategy they were cognitive, social, memory, metacognitive, and determination. The result showed that the students used all the strategies. After the researcher conducted the research, the researcher found all of the students in second semester in English department used all of strategy when learning vocabulary. The dominant strategies used by the students in Learning Vocabulary was Cognitive strategies. It also found that students usually combined one strategy with another. Combining strategies in learning vocabulary could help in making it easier to understand the vocabulary. The students combined metacognitive and cognitive, social and metacognitive, social and cognitive, determination and cognitive, memory and cognitive. It could be seen that students often combined cognitive strategies with other strategies because these strategies were easier to implement with other strategies.